Reformasi Pendidikan Islam: Tinjauan Pembelajaran Pendidikan Islam Dengan Pendekatan Kurikulum Sosial Kultural - Muchofillah, Imas (Literasi: Jurnal Ilmu Pendidikan, 2015)
Abstract Islamic Education system is currently experiencing saturated management. One of that cause is many theories that is given in Islamic Education system we must include of cultural values in order to the Islamic Education system is more enthusiastic. Because after Islam will continue to cling to the existing culture of the local community. The way to reform and reformulate a new paradigm of learning strategies that balance. By learning the balance between the cognitive (intellectual ability), affective (spiritual abilities) and psychomotor (professional abilities). Human potential as God’s gift should be developed, while the development potential in accordance with the instructions of the Lord is worship. Thus, the purpose of human events in the context of worship is in terms of the development of human potential that made him achieve the highest degree of humanity. And the high degree of humanity would look if useful to others. Because rahmatan lil’alamin in the concept of Islam is regardless of tribe, race, religion, race and class. Keywords: Reform education system, learning strategy, cultural values